Mormodes benelliana (Catasetinae), a new species from Mato Grosso, Brazil - Engels, Mathias E. (2024)
In the present study, we describe and illustrate Mormodes benelliana, a new species found in the southwest region of the Brazilian state of Mato Grosso. This species occurs as an epiphyte in the transition between the Amazon and Cerrado domains. Mormodes benelliana is similar to M. hoehnei, but differs by having smaller pseudobulbs, inflorescences longer than the pseudobulbs, conspicuous peduncle, yellowish-brown and brown-vinous striped flowers, with a large-elliptic to ovate, glabrous lip.